2000
DOI: 10.1067/mva.2000.109333
|View full text |Cite
|
Sign up to set email alerts
|

Continued experience with physical examination alone for evaluation and management of penetrating zone 2 neck injuries: Results of 145 cases

Abstract: This series confirms the earlier report indicating that patients with zone 2 penetrating neck wounds can be safely and accurately evaluated by physical examination alone to confirm or exclude vascular injury. The missed-injury rate is 0.7% (1/145) with this approach, which is comparable to arteriography in accuracy but less costly and noninvasive. Long-term follow-up is needed to confirm this management option.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
76
1
4

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(88 citation statements)
references
References 39 publications
4
76
1
4
Order By: Relevance
“…[6] Our patient had none of the symptoms above. For asymptomatic patients, there are some studies envisaging vascular exploration for selective cases in neck injuries.…”
Section: Discussionmentioning
confidence: 97%
“…[6] Our patient had none of the symptoms above. For asymptomatic patients, there are some studies envisaging vascular exploration for selective cases in neck injuries.…”
Section: Discussionmentioning
confidence: 97%
“…Specifically for zone II injuries the importance of a thorough physical examination to detect vascular injury was shown by Sekharan [12]. In the presence of hard signs including active bleeding, expanding hematoma, a bruit or thrill over the wound pulse deficit, and a central neurologic deficit corresponding to the side of the injury the patients were taken directly to the operating room.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study done by Saharan et al on 145 patients with zone II penetrating neck trauma, it was found that physical signs of vascular injury like active bleeding, expanding hematoma, bruit, pulse deficit, central neurologic deficit etc. could accurately detect vascular injury with missed injury rate of 0.7 % which is comparable to arteriography in accuracy but less costly and noninvasive [5]. The present case had no physical signs of major vessels injury; so extensive investigations were not done apart from the x ray neck to get some information on the anatomical relationship of the foreign body with other structure in the neck.…”
Section: Discussionmentioning
confidence: 99%